The influence of employment vincules for learning a federal public organization (Research, Society and Development, 2020)
The present study aims to verify the influence of different modal ties of a federal public institution in the context of learning in the organization that uses the thought model of Peter Senge, who created the model of the five learning disciplines. The method used is a descriptive case study with a quantitative approach, using a data collection instrument through a questionnaire, answered based on the Likert Scale, by a census universe of 10 (ten) employees, with treatment and statistical analysis of the data presented. Thus, after data analysis and treatment it is possible to obtain an result of partial satisfaction for all five disciplines studied, varying only a full agreement of the effective servants in the systemic thinking discipline. Therefore, it is concluded that using different modal bonds for the studied environment does not generate adverse effects on learning, even promoting a favorable environment for the process to occur.